1981
DOI: 10.1029/ja086ia03p01628
|View full text |Cite
|
Sign up to set email alerts
|

Particle signature of magnetic flux transfer events at the magnetopause

Abstract: Energetic electron (E >20 keV) and ion (E >25 keV) enhancements have been observed using the Isee 1 and 2 spacecraft during magnetic flux transfer events in the dayside magnetosheath just outside the magnetopause. The ions are seen to be streaming along the magnetic field, filling the 90°–180° pitch angle region. The electrons are more isotropic and yet exhibit slight anisotropy in the direction opposite to that of the ions. From their intensities and spectra the ions appear to be of magnetospheric origin. Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 11 publications
1
45
0
Order By: Relevance
“…2). (A similar relation between the FTE signatures and energetic particles was presented by Daly et al (1981)). The flux levels are closely similar to those observed during the previous hour when the satellite was in the exterior cusp (see Fig.…”
Section: Detailed Observationsmentioning
confidence: 59%
“…2). (A similar relation between the FTE signatures and energetic particles was presented by Daly et al (1981)). The flux levels are closely similar to those observed during the previous hour when the satellite was in the exterior cusp (see Fig.…”
Section: Detailed Observationsmentioning
confidence: 59%
“…Plasma populations originating from the magnetosphere and with a field-aligned anisotropy were first observed inside magnetosheath FTEs by Daly et al (1981), consistent with the spacecraft being on open, reconnected magnetic field lines. A parallel beam observed on open magnetic field lines in the magnetosheath implies a connection to the Southern Hemisphere, whereas an antiparallel beam implies connection to the Northern Hemisphere.…”
Section: Introductionmentioning
confidence: 72%
“…Paschmann et al (1982) also observed a bipolar B N signature when the reconnected flux tube was crossed; this was explained by a helicity which was added to the Elphic (1978, 1979) flux tube model by Sonnerup (1987). Field-aligned plasma populations originating from the opposite side of the magnetopause have been observed within FTEs (Daly et al, 1981;Paschmann et al, 1982) consistent with reconnection. The latter study noted the following "essential" features observed in all low-latitude FTEs: a southward component in the undisturbed magnetosheath magnetic field (negative B L ); a bipolar variation in B N ; an enhanced magnetic field strength |B| and an imbalance in the total pressure (p gas +B 2 /2µ 0 ) within both the flux tube and the draping region, countered by the tension in the draped magnetospheric/magnetosheath field lines.…”
Section: Introductionmentioning
confidence: 78%